2020
DOI: 10.1177/0300060520939718
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA-365 suppresses non-small-cell lung cancer metastasis and invasion in patients with bone metastasis of lung cancer

Abstract: Objective In the present investigation, we evaluated the effects of microRNA-365 (miR-365) on non-small-cell lung cancer (NSCLC) cell metastasis and invasion in patients with bone metastasis of lung cancer. Methods Blood samples from patients with NSCLC and healthy controls and the A549 adenocarcinoma cell line were included in this study. Quantitative real-time PCR and microarray were performed on blood samples. The MTT assay, luciferase reporter assay, Transwell assay, ELISA, and western blot were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Lung cancer is the most common malignant tumor and ranks the first in the world [ 1 ]. According to the cancer-related statistics released by the National Cancer Center, lung cancer has the highest morbidity and mortality in China, and about 500,000 people die from it every year [ 2 – 4 ]. Non-small-cell lung cancer (NSCLC) is the most common pathological type of lung cancer, accounting for about 85% of cases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most common malignant tumor and ranks the first in the world [ 1 ]. According to the cancer-related statistics released by the National Cancer Center, lung cancer has the highest morbidity and mortality in China, and about 500,000 people die from it every year [ 2 – 4 ]. Non-small-cell lung cancer (NSCLC) is the most common pathological type of lung cancer, accounting for about 85% of cases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and mortality of the malignant one account for a large proportion. It is reported that about 500,000 people die of pulmonary tumors each year, so this disease should be paid more attention [ 2 , 3 ]. Patients with pulmonary tumors show cough, expectoration, decreased body mass, oppression in the chest, and bloody sputum, and even carcinogenesis, which seriously affect the physical and mental health of patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β-catenin pathway [95] miR-106a miR-106a/TP53INP1 [96] miR-139-5p miR-139-5p/Notch 1 [97] miR-17-5p PTEN/PI3K/Akt [98] miR-365 NKX2-1/EGFR/PI3K [99] miR-192-5p miR-192-5p/ TRIM-44 [100] miR-886-3p miR-886-3p-PLK1/TGF-β1 pathway [101] DNA methylation DNMTs miR-886-3p-PLK1/TGF-β1 pathway [101] DNMTs WIF-1 [102] Prostate cancer ncRNA lncRNA NEAT1 CYCLINL1/CDK19/ NEAT1-1 [103] miR-940 miR-940/ARHGAP1 and FAM134A [104] miR-181b-5p miR-181b-5p/ Oncostatin M axis [105] lncRNA HOXA11-AS HOXB13/lncRNA HOXA11-AS/ IBSP [106] lncRNA PCAT6 PCAT6/IGF2BP2/IGF1R axis [107] lncRNA NEAT1 miR-205-5p/RUNX2/ SFPQ/PTBP2 axis [108] miR-378a-3p miR-378a-3p/ Dyrk1a/ Nfatc1/Angptl2 [109] Deciphering and Targeting Epigenetics in Cancer Metastasis DOI: http://dx.doi.org/10.5772/intechopen.106584…”
Section: Cancer Types Epigenetic Types Biomarkers Pathways Referencesmentioning
confidence: 99%
“…et al revealed that miR-365 was reduced in patients with bone metastasis of NSCLC, and miR-365 could suppress lung metastasis via NKX2-1/EGFR/PI3K axis[99]. Zou et Epigenetic biomarkers in bone metastases of various cancers.…”
mentioning
confidence: 99%